2018
DOI: 10.22159/ajpcr.2018.v11i7.24162
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Permeation Enhancers on the in Vitro Skin Permeation of Ketorolac Tromethamine Through Excised Rat Skin: A Mechanistic Study

Abstract: Objective: Ketorolac tromethamine (KT) is considered as a member of Non-steroidal anti-inflammatory drugs that used as an analgesic and antipyretic agent. The main aim of this research was to investigate the effect of some herbal and chemical permeation enhancers on the in vitro skin permeability of KT.Method: Ketorolac permeability experiments through rat skin pre-treated with some of permeation enhancers, namely urea, eucalyptus oil, olive oil, and menthol, were performed in fabricated Franz diffusion cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Conversely, olive oil is less effective than most terpenes, certain surfactants, and organic solvents. In vitro permeation studies have reported a lower enhancement activity of olive oil in the permeation of ketorolac as compared to limonene, cineole, menthol, and eucalyptus oil from solution and reservoir transdermal patches [59,74]. Moreover, the in vitro and ex vivo studies carried out by Hussain et al [25] and Maniyar and Kokare [85] found it to be less effective than turpentine oil [25] and peppermint oil [85] in the permeation of diclofenac potassium and lopinavir from a gel and liposome, respectively.…”
Section: Olive Oilmentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, olive oil is less effective than most terpenes, certain surfactants, and organic solvents. In vitro permeation studies have reported a lower enhancement activity of olive oil in the permeation of ketorolac as compared to limonene, cineole, menthol, and eucalyptus oil from solution and reservoir transdermal patches [59,74]. Moreover, the in vitro and ex vivo studies carried out by Hussain et al [25] and Maniyar and Kokare [85] found it to be less effective than turpentine oil [25] and peppermint oil [85] in the permeation of diclofenac potassium and lopinavir from a gel and liposome, respectively.…”
Section: Olive Oilmentioning
confidence: 99%
“…The dominant mechanism of the penetration of eucalyptus oil is the partitioning of the essential oil into the skin, as reported by Chi-Hsien [57] during the formulation of a photosensitizer microemulsion and El-Maghraby et al [58] during the mutual transdermal administration of indomethacin and benzocaine microemulsions. Eucalyptus oil was also used in the formulation of miconazole and ketorolac solutions and was found to exert its permeation enhancement activity by several mechanisms, i.e., lipid fluidization, disruption lipid structure, and irreversible keratin denaturation in SC, resulting in higher enhancement ratios [ER] of flux [ERF], diffusion [ERD], and permeability [ERP] as compared to hydrated skin [59,60]. The fluidization mechanism of eucalyptus oil was exploited in the enhancement of felodipine permeation from a niosome formulation [61].…”
Section: Eucalyptus Oilmentioning
confidence: 99%
See 3 more Smart Citations